Influence of Word of Mouth, Store Atmosphere, Location, and Service Quality on Purchasing Decisions for MSME Product - Farhani, Ahmad; Jamiah, Jamiah; Hayati, Rahmi; Taupik, Muhammad (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the influence of Word of Mouth, Store Atmosphere, Location, and Service Quality on purchasing decisions for MSME (Micro, Small, and Medium Enterprises) products at MM Food Court Tabalong. The research employs a quantitative method using a multiple linear regression analysis approach. Data sources were obtained through questionnaires distributed to 67 respondents, who were visitors to MM Food Court Tabalong. The results show that Word of Mouth, Location, and Service Quality have a significant positive influence on purchasing decisions for MSME products at MM Food Court Tabalong, as indicated by positive regression coefficients. On the other hand, Store Atmosphere did not show a significant effect on purchasing decisions. Based on the analysis, it is found that the combination of these four variables contributes 41.6% to purchasing decisions, while the remaining 59.4% is influenced by other factors not examined in this study. This study suggests that MSME managers at MM Food Court Tabalong should focus more on improving the quality of Word of Mouth, strategic location, and service quality. Meanwhile, efforts on Store Atmosphere should be maintained and preserved to encourage consumers to continue making purchasing decisions.